(untitled) (Modern education and development, 2024)
Currently, gout is a serious medical problem, and the number of patients with gouty arthritis is constantly growing in all countries with a high standard of living. Asymptomatic hyperuricemia and the high prevalence of gout (1-3%) among the population are important risk factors for cardiovascular diseases. The aim of the study is to assess the association of hyperuricemia with lipid profile disorders in patients with arterial hypertension, gout, and asymptomatic hyperuricemia. Nevertheless, the problem of using antihypertensive drugs in gout in Uzbekistan remains open. Thus, the analysis of the latest literature shows that at present, the problem of early diagnosis and modern treatment of arterial hypertension in patients with gout and asymptomatic hyperuricemia remains open.